Thymidylate Synthetase as Target Enzyme for the Inhibitory Activity of 5-Substituted 2'-Deoxyuridines on Mouse Leukemia L1210 Cell Growth - DE CLERCQ, E.; BALZARINI, J.; TORRENCE, P.F.; MERTES, M.P.; SCHMIDT, C.L.; SHUGAR, D.; BARR, P.J.; JONES, A.S.; VERHELST, G.; WALKER, R.T. (Molecular pharmacology, 1981)
A series of 26 5-substituted 2'-deoxyuridines (dUrd), including various dUrd analogues (viz. 5-(1-chlorovinyl)-dUrd, E-5-(2-bromovinyl)-dUrd, 5-azidomethyl-dUrd, 5-methyl-thiomethyl-dUrd, 5-propynyloxy-dUrd), which have never been the subject of extensive antitumor studies, were evaluated for their inhibitory effects on L1210 cell proliferation. The most effective inhibitors were (in order of decreasing activity): 5-fluoro-dUrd > 5-trifluoromethyl-dUrd > 5-nitro-dUrd (5'-monophosphate) > 5-ethynyl-dUrd > 5-formyl-dUrd > 5-(1-chlorovinyl)-dUrd. Their 50% inhibitory dose (ID50) fell within the 0.5-0.001 µg/m1 range. These and several other dUrd analogues (i.e., 5-cyano-dUrd, 5-thiocyano-dUrd via 5-mercapto-dUrd 5'-monophosphate, and the 5-oxime of 5-formyl-dUrd) have been recognized previously as potent and/or selective inhibitors of thymidylate synthetase. As could be expected from specific thymidylate synthetase inhibitors, all nine compounds were far more inhibitory to [2-14C]dUrd incorporation into host cell DNA than to [methyl-3H]dThd incorporation, and their inhibitory effects on L1210 cell proliferation were more readily reversed by dThd than by dUrd. The other 17 dUrd analogues, all of which had ID50 values for L1210 cell growth that were greater than 1 µg/ml, did not discriminate between [2-14C]dUrd and [methyl-3H]dThd incorporation, and their inhibitory effects on L1210 cell growth were reversed equally well by dThd and dUrd, or not reversed at all. For the nine dUrd analogues which could be considered as thymidylate synthetase inhibitors, there was a strong correlation (R = 0.904) between their inhibitory effect on tumor cell growth, on the one hand, and their relatively greater inhibition of [2-14C]dUrd incorporation and reversal of antitumor activity by dThd, on the other. This correlation points to thymidylate synthetase as the principal, if not the sole, intracellular target for the inhibitory activity of 5-substituted 2'-deoxyuridines on L1210 cell growth. ACKNOWLEDGMENTS We thank Lizette Van Berckelaer for excellent technical assistance and Paul Darius for help with the statistical analysis of the data.